Studi Kinetika Pada Proses Elektrokoagulasi Zat Warna Metilen Biru - Saputra, Andrian; Tiandho, Yuant; Afriani, Fitri (Jurusan Fisika, Universitas Bangka Belitung, 2022)
The main problem that is generally faced by textile industry players is related to the large amount of liquid waste produced. Liquid waste from methylene blue dye cannot be discharged directly into the water because it has a high solubility level and is non-biodegradable. Therefore, in this study, treatment of methylene blue dye waste was carried out using an easy-to-apply electrocoagulation method with a high level of efficiency for separating pollutant levels in wastewater. The next step is the decolorization of methylene blue dye waste with a given voltage variation of 20,25, and 30 volts and variations in the time used for 1,3,5,10,15,20,25, and 30 minutes. Based on the results of the study, shows that the greater the electric voltage and the longer the electrocoagulation process is carried out, the higher the decolorization value produced by the methylene blue dye waste. The results of the decolorization obtained were then continued by analyzing the reaction rate which showed a change in the concentration of methylene blue which was directly proportional to the given time. The reaction rate analysis was carried out using a reaction kinetics model, namely first order, second order, and BMG. Based on the values generated from the three reaction kinetics models, the BMG kinetic model is the best reaction kinetics model because it has a high coefficient determination (R2) of 0,999.